Penerapan Simple Additive Weighting Sebagai Sistem Pendukung Keputusan Pemilihan dan Penentuan Siswa Terbaik - Gulo, Nitema; Purba, Eduard Hotman; Supriyanti, Dedeh; Rakhmansyah, Mohamad (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2025)
The purpose of this study is to design and create a decision support system for SMA Negeri 1 Cilegon, also known as SMANCIL. The use of the Simple Additive Weighting method to achieve the objectives of the study. So far, certain methods have not been used to select the best students, so that the decisions made are considered non-objective and not on target. Therefore, a decision support system is expected to help in making decisions about the best students. This study will investigate the case of finding the best alternative based on predetermined criteria. To calculate the weighted sum of the performance ratings for each alternative in all attributes, the SAW method is needed. By using the SAW method, several criteria are calculated to provide recommendations for the desired students. The ranking results show V6 = 0.97 and V28 = 1.00. Based on these results, it can be concluded that of all the specified criteria, V28 is the best student choice. This study is expected to produce a design for selecting the best students that will help teachers choose the best students according to their wishes.